2020
DOI: 10.1088/1361-6501/abae8f
|View full text |Cite
|
Sign up to set email alerts
|

Robust image segmentation for feature extraction from internal combustion engine in-cylinder images

Abstract: In-cylinder imaging diagnostics for internal combustion engines provide rich information on the structure and evolution of reaction zone features, which affect both engine out emissions and efficiency. However, the most common analysis of in-cylinder combustion luminosity imaging considers ensemble averaged images, which are not suitable for characterizing processes that vary significantly between cycles, such as ignition and soot formation and oxidation. Here, a robust image segmentation algorithm is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Most of the traditional image registration schemes consist of three main steps: feature extraction, feature matching, and image transformation [1,2]. The most frequently used image features include regional features [3][4][5][6], line features [7,8], and point features [9][10][11][12]. These features generally remain unchanged following rotation, scaling, and tilt transformations, and can remain stable under conditions such as ambient noise and grayscale stretching.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the traditional image registration schemes consist of three main steps: feature extraction, feature matching, and image transformation [1,2]. The most frequently used image features include regional features [3][4][5][6], line features [7,8], and point features [9][10][11][12]. These features generally remain unchanged following rotation, scaling, and tilt transformations, and can remain stable under conditions such as ambient noise and grayscale stretching.…”
Section: Related Workmentioning
confidence: 99%
“…The authors reported an attempt of using an automatic thresholding technique for jet tracking that was unsuccessful due to differences in illumination and background, which required further processing based on the mean and standard deviation of the pixel intensity of images from each combustion cycle. A method that combines dynamic thresholding, region size filtering and watershed segmentation has been proposed in Rochussen and Kirchen, 13 which was compared to global thresholding and Otsu's method and achieved a performance increase. It must be noted that such method requires the set-up of a series of parameters which must be tuned for the specific application.…”
Section: Introductionmentioning
confidence: 99%